Aerodynamic shape and drag scaling law of a flexible fibre in a flowing medium - Bo-Hua Sun; Xiao-Lin Guo (Theoretical and Applied Mechanics Letters, 2023)
The study of a flexible body immersed in a flowing medium is one of the best way to find its aerodynamic shape. This Letter revisited the problem that was first studied by Alben et al. (Nature 420, 479–481, 2002). To determine the aerodynamic shape of the fibre, a simpler approach is proposed. A universal drag scaling law is obtained and the universality of the Alben-Shelley-Zhang scaling law is confirmed by using dimensional analysis. A complete Maple code is provided for finding aerodynamic shape of the fibre in the flowing medium.